Replication Data for: Cassava Breeding I: The value of breeding value - Ceballos, H.; Pérez, Juan C.; Joaqui B., Orlando; Lenis Calderon, Jorge Iván; Morante, Nelson; Calle, Fernando; Hershey, Clair H. (2016)
Phenotypic data from clonal evaluation trials in sub-humid environment of Colombia